Prescribe, Review, Now!: an assessment of adequate PRN analgesia and associated laxative prescribing using Hospital Electronic Prescribing and Medicines Administration (HEPMA) - Matthew McMillan; Alexandra Jayne Burgess (BMJ Open Quality)
Introduction On HEPMA there is no way to notify a prescriber if patients are regularly accessing PRN (as-required) analgesia. We aimed to assess how well PRN analgesia use is identified, the WHO analgesic ladder and whether laxatives were prescribed with opioid analgesia.Methods 3 data collection cycles were carried out for all medical inpatients between February-April 2022. Medication was reviewed to determine: 1) PRN analgesia prescribed? 2) Is the patient accessing it >3 times in 24hours? 3) Con-current laxatives prescribed. Between each cycle, an intervention was implemented. Intervention 1: Posters were placed on each ward and circulated electronically as a cue to a review and change analgesia “Prescribe. Review. Now!” Intervention 2: A presentation on data, the WHO analgesic ladder and laxative prescribing was created, and circulated.Results See Figure 1 – Comparison of prescribing per cycle. Cycle 1 - 167 inpatients surveyed, 58%female, 42%male, mean age 78(±13.4). Cycle 2 - 159 inpatients,65% female, 35% male, mean age of 77 (±15.7). Cycle 3 - 157 inpatients, 62% female, 38% male, mean age 78 (±15.7). Adequate prescriptions on HEPMA improved by a total of 31% (p<0.005), over 3 cycles and 2 interventions.Conclusions After each intervention there was a significant statistical improvement in prescribing analgesia and laxatives. However, there is still room for further improvement, especially in ensuring adequate laxative cover is prescribed for all patients either >65 years old, or those on opioid-based analgesia. Visual reminders on wards of regularly checking PRN medication showed to be an effective intervention.